Perlindungan Hukum Hak Merek atas Peredaran Skincare Palsu Glow Glowing serta Dampaknya terhadap Konsumen - Santi Halimatusaa’adah; Yuna Nasywa; Naura Jasmine Aulia; Ikhwan Aulia Fatahillah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the legal protection for the trademark holder of Glow Glowing skincare against counterfeiting, the forms of compensation claims that can be filed by the legitimate owner regarding the circulation of illegal products, and the impact of such counterfeiting on brand image and consumer trust. This research uses a normative juridical legal method with statutory and case approaches. Data analysis was carried out descriptively and qualitatively to explain legal facts comprehensively. The results show that the protection of the Glow Glowing trademark is applied through preventive instruments via registration with the Directorate General of Intellectual Property (DJKI) and repressive protection through criminal enforcement based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. As a form of loss settlement, the legitimate brand owner can file a civil lawsuit at the Commercial Court to demand material compensation, such as a decrease in sales turnover, as well as immaterial losses in the form of damaged brand reputation due to the circulation of these illegal cosmetics. Furthermore, the circulation of counterfeit skincare is proven to have a destructive impact that drastically triggers a decline in consumer trust and damages the brand image in the market.